(untitled) (Journal of Science and Technology, 2016)
Sustained-release theophylline tablets were prepared using mucuna gum as a hydrophilic polymer. The gum was found to prolong drug release from the product. The release rate was dependent on the gelation rate with resultant dissolution and diffusion of the active ingredient as was observed from the dissolution and liquid penetration tests carried out. The release rate was dependent on the concentration of the gum in the tablets.